Upaya Penanggulangan Kejahatan Perdagangan Anak di Bandar Lampung - Niken Nurhadz Febriyani; Heni Siswanto; Maya Shafira; Maroni Maroni; Aisyah Muda Cemerlang (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
Child trafficking is an organized crime that exploits children in various forms and is still prevalent in Indonesia. This continues despite law enforcement efforts and regulations on child protection in an attempt to combat it. The purpose of this study is to examine the efforts made in handling child trafficking crimes in Bandar Lampung City through a case study approach to Case Number 311/Pid.Sus/2024/PN Tjk. The methods used are a normative legal approach and a legal approach. The findings of the study indicate that the crime prevention strategy is pursued through penal mechanisms with the application of criminal provisions based on Article 83 of Law Number 17 of 2016 of the Republic of Indonesia, which stipulates Government Regulation in Lieu of Law Number 1 of 2016 as the second amendment to Law Number 23 of 2002 concerning Child Protection, as well as a non penal approach in the form of strengthening supervision, optimizing the Task Force on Human Trafficking Crimes, increasing public awareness, active reporting, supporting victim rehabilitation, and education to strengthen child protection and resilience.